INFLUENCE ANALYSIS OF MURABAHAH AND MUSYARAKAH RECEIVABLES WITH MODERATED REGRESSION ANALYSIS METHOD - Elfiswandi Elfiswandi; Muhammad Fikri Ramadhan; Fitri Indah Mayang Sari; Desi Rosalina (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
This study aims to determine how influential Murabahah and Musyarakah receivables are on the profitability of Islamic banks with non-performing financing as a moderating variable. The population in this study are Islamic banks in Indonesia from 2015 to 2019. The sample for this study is 14 banks. This research methodology uses a saturated sample, namely where the entire population is sampled. data analysis method using panel data regression, EVIEWS. Based on the results of this study. Murabaha receivables have a negative effect on the profitability of Islamic banks. Musyarakah financing affects the Profitability of Islamic Banks. Murabahah Receivables and Musyarakah Financing jointly affect the Profitability of Islamic Banks. Non-performing financing weakens the relationship between Murabahah Receivables and Sharia Bank Profitability. Non performing financing strengthens the relationship between Musyarakah Financing and Sharia Bank Profitability